2019
DOI: 10.3389/fevo.2019.00088
|View full text |Cite
|
Sign up to set email alerts
|

Bartonella Bacteria in Urban Rats: A Movement From the Jungles of Southeast Asia to Metropoles Around the Globe

Abstract: Despite the widespread recognition of the risks of disease transmission associated with international trade in domestic animals and movement of exotic animals, less is known about the role of rats in carrying pathogens between continents. The genus Bartonella, a highly prevalent and extremely diverse group of bacteria, includes species that are excellent sentinel organisms for evaluating the transoceanic and intra-continental movement of the pathogens carried by rats of the genus Rattus. The patterns of spatia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 101 publications
(236 reference statements)
1
25
0
2
Order By: Relevance
“…Bartonella spp. are a genus of zoonotic, intracellular bacteria that infect erythrocytes and endothelial cells (1). Wild rodents are an important reservoir for Bartonella spp.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bartonella spp. are a genus of zoonotic, intracellular bacteria that infect erythrocytes and endothelial cells (1). Wild rodents are an important reservoir for Bartonella spp.…”
Section: Introductionmentioning
confidence: 99%
“…Wild rodents are an important reservoir for Bartonella spp. and infections in these species are persistent and asymptomatic (1). In people, however, infection with rodent-associated strains can result in septicemia with a broad range of clinical signs (1,2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, no previous studies investigated residency at seaport areas as potential risk factor for human exposure to Bartonella spp. Kosoy et al [ 22 ] suggested that influx of imported rats by ships causes a higher Bartonella spp. infection rate in rats located in seaports compared with the ones in mainland.…”
Section: Discussionmentioning
confidence: 99%
“…This is further supported by the fact that the animal-related factors of our study failed to explain antibody occurrence, suggesting a universal source of infection, such as the ubiquitous fleas. As IFAT is unable to distinguish B. henseleae from species commonly identified in rodents such as B. tribocorum or B. elizabethae [ 22 , 25 ], exposure cannot be attributed to specific Bartonella species. Rat population size, and other ecological factors may also have an impact in the flea-borne Bartonella spp.…”
Section: Discussionmentioning
confidence: 99%